Predictors of competency on delivery care service among final year undergraduate midwifery students in higher education institutions of Ethiopia, 2019: A cross sectional study - Dereje Nibret Gessesse; Birhanu Wubale Yirdaw; Dawit Gebeyehu Mekonen (Elsevier, 2021)
Background: Competence is the documentation of an acceptable level of performance, through a process of structured assessment. Focusing on generating highly competent midwives with essential skills, more specifically on childbirth care services helps to improve maternal and newborn health outcomes. This study was aimed to assess determinants of competency on delivery care among newly graduated bachelor midwifery students in Amhara regional state Higher Education Institutions, Ethiopia, 2019. Method: Institution-based cross-sectional study was conducted. A total of 420 participants were included in the study. A structured, pretested and self-administered questionnaire was used to collect the data. A stratified random sampling technique was employed to select the study participants. The data was entered into Epi info version 7.0 and then exported to SPSS version 20.0 for analysis. Both bivariate and multivariable logistic regression models were fitted. Crude and Adjusted Odds ratio with 95% confidence interval has been computed and variables with p-value < 0.05 were considered statistically significant. Result: The overall proportion of delivery care competency was 28.8%. Midwives' choice to midwifery profession as their first field of study [AOR: 3.2, 95%CI; (1.6-6.5)], teachers who allocate enough time at clinical practice sites [AOR: 2.5, 95%CI; (1.5-4.2)], and absence of practitioners from other disciplines [AOR: 2.4, 95%CI; (1.4-4.1)], were significantly associated. Conclusion: The overall proportion of delivery care competency was found to be low. Insuring regular mentoring and supervision, staying with students at the practical sites and avoiding attachment sites for clinical practice crowded by other discipline students are strongly recommended.